مدى فهم الطلبة للأحكام النحوية = The extent of Arabic grammar understanding - Abdul Rahim, Abdul Hadi; Mat Isa, Mohd Farhan; Khalib, Khairul Akbar; Noor Hazlee, Nor Hazleena (GBSE Global, 2019)
إنَّ الأحكام النحوية تعتبر عنصرا من العناصر المهمة في تعلّم اللغة العربية، خاصّة حول بنية كلمتها معربةً ومبنيةً (عبد الهادي، 2017م). وهدف هذا البحث لكشف مدى فهم الطلبة في الأحكام النحوية أثناء تعلمهم في اللغة العربية. تتكوّن عينة البحث من الّذين يدرسون في المركز التّمهيدي للكلية الجامعية الإسلامية بسلانجور مما ينضمّ خمسين (50) طالب الجامعة وخمسين (50) طالب المدرسة. ويتبع الباحثون منهجيْن أي وصفي وتحليلي؛ حيث يتصف المنهج الوصفي وصفاً كاملاً ودقيقاً عن النظريات من المصادر المتعددة. وبالتّالي قام الباحثون بتحليل اكتشاف فهم الطلبة بناءً على النّتائج من الاستبانة باستخدام البرنامج SPSS. ومن النّتائج التي توصّلت إليها الدّراسة مدى فهم الطلبة للأحكام النحوية في تعلّم اللغة العربية. ***************************************************************************************** The law of Arabic Grammar is an important element in learning the Arabic language, especially the inflective and structure of the word (Abdul Hadi, 2017). The aim of this research is to uncover the implementation of Arabic Grammar Law in students learning> The research sample consists of 60 students of the matriculation centre of the Islamic University College Selangor, and sixty (60) students from secondary school. The researchers follow two descriptive and analytical approaches in this research. The descriptive approach has comprised of theories from multiple sources. Thus, the researchers analysed the result based on the understanding of students using Arabic Grammar Law. The researchers distribute a questionnaire and interpret it using the SPSS program. As a result, the researchers could halt the understanding of Arabic grammatical rules in among the students.